ESTABLISHING THE STATUS OF RESPONSIBILITY TO PROTECT (R2P) AS CUSTOMARY INTERNATIONAL LAW AND ITS ROLE IN PREVENTING MASS ATROCITIES - Sigar Aji Poerana; Irawati Handayani (Padjadjaran Journal of International Law, 2021)
ABSTRACTResponsibility to Protect (R2P) was unanimously adopted and is articulated in paragraphs 138 and 139 of General Assembly Resolution A/Res/60/1. On the one hand, R2P has presumed a new name for humanitarian intervention that is still debatable in international law. On the other hand, R2P attempts to connect State’s sovereignty and responsibility to protect human rights. R2P recognizes State’s sovereignty while bestowing States the primary responsibility to protect human rights and allowing the international community to intervene if States fail to fulfill their obligation. Considering the original idea of R2P is to protect human rights, the essential issue that should be addressed is the position of R2P as source of international law. Suppose States should implement the R2P without a prior commitment to a treaty, which sources of international law that can underlie the legal basis for R2P? This article argues that R2P can fulfill the criteria of customary international law based on the notion of ‘Grotian moment,’ which ‘compensates’ R2P from the traditional burden of state practice and opinio juris since R2P is a paradigm-shifting development in which new rules and doctrines of custom emerge with unusual rapidity and acceptance. Further, this article also highlights the importance of responsibility to prevent, which is one of the pillars of R2P, and argues that commitment to prevent is the “heart” of R2P. It is argued that such responsibility is vital in saving States from avoidable conflicts and from the trouble in responding to mass atrocities and rebuilding the affected population. Keywords: Customary International Law, Grotian Moment, Responsibility to Protect, Responsibility to Prevent, Sources of International Law ABSTRAKResponsibility to Protect (R2P) diadopsi dengan suara bulat dan dicantumkan dalam paragraf 138 dan 139 Resolusi Majelis Umum A/Res/60/1. Di satu sisi, R2P dianggap sebagai nama baru untuk intervensi kemanusiaan yang masih diperdebatkan dalam hukum internasional. Di sisi lain, R2P berupaya untuk menjembatani kedaulatan negara dan tanggung jawab untuk melindungi Hak Asasi Manusia (HAM). R2P tetap mengakui kedaulatan negara dan memberikan tanggung jawab utama kepada negara untuk melindungi HAM, namun mengizinkan masyarakat internasional untuk mengintervensi jika negara gagal memenuhi kewajibannya. Mengingat ide awal R2P adalah untuk melindungi HAM, maka isu penting yang harus ditelaah adalah posisi R2P sebagai sumber hukum internasional. Misalnya, negara harus mengimplementasikan R2P tanpa komitmen terlebih dahulu terhadap suatu perjanjian internasional, sumber hukum internasional manakah yang dapat mendasari pelaksanaan R2P? Artikel ini berpendapat bahwa R2P dapat memenuhi kriteria hukum kebiasaan internasional berdasarkan konsep ‘Grotian moment', yang 'mengkompensasi' R2P dari beban tradisional state practice dan opinio juris karena R2P merupakan perkembangan yang mengubah paradigma yang mengakibatkan aturan baru dan doktrin kebiasaan muncul dengan laju dan penerimaan yang luar biasa. Lebih lanjut, artikel ini juga menyoroti pentingnya tanggung jawab untuk mencegah, yang merupakan salah satu pilar dari R2P, dan berpendapat bahwa komitmen untuk mencegah adalah esensi dari R2P. Tanggung jawab untuk mencegah sangat penting dalam menjauhkan negara dari konflik yang dapat dihindari dan dari kesulitan dalam merespon krisis kemanusiaan dan membangun kembali penduduk yang terkena dampaknya. Kata Kunci: Grotian Moment, Hukum Kebiasaan Internasional, Tanggung Jawab untuk Melindungi, Tanggung Jawab untuk Mencegah, Sumber Hukum Internasional